2022
DOI: 10.1007/s00423-022-02520-w
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted minimally invasive Ivor Lewis esophagectomy within the prospective multicenter German da Vinci Xi registry trial

Abstract: Purpose Robotic-assisted minimally invasive esophagectomy (RAMIE) has become one standard approach for the operative treatment of esophageal tumors at specialized centers. Here, we report the results of a prospective multicenter registry for standardized RAMIE. Methods The German da Vinci Xi registry trial included all consecutive patients who underwent RAMIE at five tertiary university centers between Oct 17, 2017, and Jun 5, 2020. RAMIE was performed acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Our study cohort showed an ECCG AL type II in 21 of 157 patients (13.4%) after IL RAMIE. This corresponds to the data by van der Sluis et al, Pointer et al, and Egberts et al, who report a leak rate of 11, 13.5, and 13.2%, respectively [26][27][28]. Compared to the studies of the DCDP Database and the ESO Benchmark database which report an AL rate of 15 and 15.9%, IL RAMIE showed a lower AL rate.…”
Section: Discussionsupporting
confidence: 85%
“…Our study cohort showed an ECCG AL type II in 21 of 157 patients (13.4%) after IL RAMIE. This corresponds to the data by van der Sluis et al, Pointer et al, and Egberts et al, who report a leak rate of 11, 13.5, and 13.2%, respectively [26][27][28]. Compared to the studies of the DCDP Database and the ESO Benchmark database which report an AL rate of 15 and 15.9%, IL RAMIE showed a lower AL rate.…”
Section: Discussionsupporting
confidence: 85%
“…Previously, it has been shown that early detection of PIC is essential not only for the treatment of complications but also for patient survival [ 20 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. PICs, according to the definition used for this paper, include surgical site infections, pneumonia, pleural empyema, leakage or necrosis of the gastric conduit, and anastomotic leakage [ 33 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, patients with a previous history of smoking seem to be more susceptible to postoperative pulmonary complications [ 42 ]. It was postulated that less invasive and shorter procedures, especially for the thoracic part of the procedure, would cause fewer pulmonary infectious complications [ 34 , 43 , 44 , 45 , 46 ]. Glatz et al found HMIE to cause lesser pulmonary and overall complications, compared to OE, without taking infectious parameters into consideration [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that 51 cases were the baseline to achieve acceptable surgical outcomes and proficiency and 73 cases were needed to further make a difference in blood loss and LN yield (49). In comparison, the 22nd case represented the inflection point, resulting in less blood loss, shorter operative time, and a lower rate of postoperative pneumonia in German multicenter research (29). We thus speculate the Upper GI International Robotic Association (URIGA) structured training pathway implemented in Germany may be a crucial factor.…”
Section: Learning Curve Of Raile For Thoracic Surgeonsmentioning
confidence: 93%
“…Common complications related to esophagectomy include anastomotic leakage, pulmonary complications (such as pneumonia, respiratory failure, pleural effusion, and pneumothorax), vocal cord paralysis, severe cardiac complications (mainly arrhythmia), chylothorax, and wound infection. The anastomotic leak rate ranges from 1.9 to 19.6% (4,8,11,22,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Despite using different anastomotic methods, some centers had leak incidences of less than 5%, suggesting the underlying importance of personal proficiency.…”
Section: An Overview Of Short-term Outcomes Of Railementioning
confidence: 99%